2005
DOI: 10.1002/adma.200500551
|View full text |Cite
|
Sign up to set email alerts
|

Ultranarrow ZnSe Nanorods and Nanowires: Structure, Spectroscopy, and One‐Dimensional Properties

Abstract: Zinc selenide is an important wide-bandgap (2.8 eV) material [1] with a broad range of potential applications. It exhibits interesting photophysical phenomena involving green-blue light emission and high transmission in the infrared and the visible electromagnetic spectrum.[2] Nanoparticles of ZnSe, via quantum confinement, shape, size and surface dependent effects, hold promise for tuning the optical properties and for assembling the particles in nanoscale structures. ZnSe has been studied to a lesser extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 161 publications
(176 citation statements)
references
References 32 publications
7
169
0
Order By: Relevance
“…5c). [75] In all the examples mentioned above, very strong quantum confinement effects were observed, testifying to the crystallinity and small diameter of the wires. While it is true that oriented attachment is easier to obtain on structures possessing an anisotropic lattice, such as wurtzite, recent experiments have demonstrated that cubic structures can also undergo oriented attachment in spectacular ways.…”
Section: Oriented Attachmentmentioning
confidence: 92%
See 2 more Smart Citations
“…5c). [75] In all the examples mentioned above, very strong quantum confinement effects were observed, testifying to the crystallinity and small diameter of the wires. While it is true that oriented attachment is easier to obtain on structures possessing an anisotropic lattice, such as wurtzite, recent experiments have demonstrated that cubic structures can also undergo oriented attachment in spectacular ways.…”
Section: Oriented Attachmentmentioning
confidence: 92%
“…[73] c) HRTEM image of ZnSe nanowires formed by reacting zinc acetate with selenourea in the presence of octadecylamine. [75] d,e) HRTEM and TEM images of PbSe nanowires formed by reacting lead oleate with trioctylphosphine selenide in the presence of oleic acid, and oleic acid and tetradecylphosphonic acid, respectively. [76] f,g) TEM and HRTEM images of PbS nanowires formed by thermal decomposition of lead hexadecylxanthate in the presence of trioctylamine.…”
Section: Future Directions and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the resultant devices may be improved because single crystal nanorod or nanowire arrays can offer direct pathways for carrier and thus accelerate transport rate and charge collection [11,15,16]. Many II-IV group nanorods, such as CdS, CdSe, CdTe, ZnS, ZnSe, and ZnTe, have been successfully synthesized in colloidal solutions [17][18][19][20][21][22]. However, except ZnO [23], there are only a few reports that describe the fabrication of aligned II-IV nanorod or nanowire arrays without involving of catalyst and/or templates [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis makes use of long-chain alkylamines as liganding solvents, which enable a low temperature, one step, bench-top reaction of the relatively innocuous zinc acetate and selenourea precursors, to produce ZnSe nanowires. [24] The nanowires are of very uniform width with an average diameter of 1.3 ± 0.1 nm and length of 100-200 nm (an aspect ratio of ∼ 75-150). The side-byside spacing between the wires is 2.0 ± 0.1 nm as measured from transmission electron microscopy (TEM) images, and can be varied by changing the chain length of the amine ligand.…”
mentioning
confidence: 99%